Classic Vulvar Intraepithelial Neoplasia With Superimposed Lichen Simplex Chronicus: A Unique Variant Mimicking Differentiated Vulvar Intraepithelial Neoplasia. (March 2019) - Watkins, Jaclyn C.; Yang, Eric; Crum, Christopher P.; Herfs, Michael; Gheit, Tarik; Tommasino, Massimo; Nucci, Marisa R.
Abstract : High-grade vulvar intraepithelial neoplasia, a precursor lesion to vulvar squamous cell carcinoma, is subdivided into 2 types, classic or usual vulvar intraepithelial neoplasia (CVIN) and differentiated vulvar intraepithelial neoplasia (DVIN). CVIN, which is a human papilloma virus (HPV)-dependent lesion, is typically distinguished from DVIN, a p53 mutation-dependent process, by its distinct histomorphologic and immunohistochemical characteristics. However, distinguishing between the 2 entities becomes challenging in cases of CVIN with superimposed inflammatory changes, especially lichen simplex chronicus (LSC). Twelve cases of DVIN, 9 cases of LSC, and 9 cases of CVIN with superimposed LSC were assessed for a number of morphologic features, including hyperkeratosis, hypergranulosis, acanthosis, hypercellularity, abnormal maturation (i.e. abnormal keratinization close to the base and/or dyskeratosis), hyperchromasia, and basal atypia. Immunohistochemistry for p53, p16, and MIB-1 was performed for all cases. When sufficient tissue was available, HPV genotyping was performed for cases of CVIN with superimposed LSC. DVIN uniformly demonstrated abnormal maturation, and atypia involving the basal cell layer; they were all p16 negative and demonstrated p53 positivity of moderate to strong intensity in a basal and parabasal distribution. CVIN with superimposed LSC frequently displayed hyperchromasia involving the basal 3 to 4 cell layers, basal to full-thickness atypia, and apoptosis. CVIN with superimposed LSC demonstrated intense p16 positivity extending from the basal cells to the mid-epithelium and a reduction or loss of staining in maturing keratinocytes. P53 staining revealed a unique pattern of parabasal and mid-epithelial weak to moderate staining with sparing of the basal layer. Cases of LSC demonstrated heterogenous p53 positivity and were negative for p16. MIB-1 staining showed a similar range of positivity for all diagnoses. HPV genotyping revealed HPV 16 in all 5 cases of CVIN with LSC that underwent testing. We conclude that, although CVIN with superimposed LSC can closely resemble DVIN, morphologic features such as nuclear hyperchromasia uniformly involving the basal 3 to 4 cell layers, apoptosis, and absent or less pronounced cytoplasmic maturation are more suggestive of CVIN with superimposed LSC. In cases where the morphology remains ambiguous, immunohistochemistry for both p16 and p53 can be helpful. In particular, p53 parabasal and mid-epithelial staining without involvement of the basal layer appears to be a characteristic finding in CVIN with superimposed LSC. MIB-1 staining is of little utility in distinguishing between these entities and should not be routinely performed.